Clima organizacional y desempeño laboral en Macor Ingenieros SCRL, Iquitos 2023 - Anaya Matute, Nayely Dianety (2023)
The general objective of the study is to determine the relationship between the organizational climate and the work performance of the workers of the consulting firm Macor Ingenieros, Iquitos 2023. The approach used would be quantitative, the results will be presented with data that have numerical values; for (Hernández-Sampieri, 2018) “The quantitative approach finds the precise way to address (specified and delimited approach) and a precise map or GPS (bounded design)” In our correlative result, 0.656** was obtained Pearson, this would indicate a classification positive means; We also see that the bilateral sigma value is 0.002 < 0.05, which would indicate that it is significant due to the decision rule. We conclude that there is a significant relationship between the variables studied.